PENGARUH MODEL POLYA TERHADAP PENINGKATAN KEMAMPUAN SISWA DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA KELAS 5 SDN 067258 MEDAN AMPLAS - Naibaho, Jennifer Divia; Simbolon, Naeklan; Simanungkalit, Erlinda; Simanjuntak, Eva Betty; Ambarita, Dodi F. Pandimun (Universitas Negeri Medan, 2024)
This research aims to determine the effect of the Polya Model on improving students' abilities in solving fifth grade mathematics story problems at SDN 067258 Medan Amplas. This research method is quasi-experimental with a nonequivalent control group design. The population is all class V students at SDN 067258 Medan Amplas, which are divided into two classes, namely V-A and V-B. Class V-A is the control class which is treated using the Conventional Model and class V-B is the experimental class which is treated using the Polya Model. The instrument used is a cognitive learning test in the form of an essay with 10 questions. Based on the results of data processing, the pre-test data obtained an average score for control class students of 36.81 and experimental class 27.71. After being given treatment, the control class obtained an average of 52.72 and the experimental class obtained an average of 76.84. The results of the post-test t test at the significance level Î±= 0.05 obtained tcount = 5.168 and ttable = 1.168, so tcount > ttable so that the hypothesis (Ha) is accepted and the hypothesis (Ho) is rejected. Based on this, it was concluded that there was a significant influence of using the Polya Model on increasing students' abilities in solving class V mathematics story problems at SDN 067258 Medan Amplas.Keywords: Polya model, learning outcomes, story problems